The sound of maracas (tribute to Ailton Krenak): indigenous medical practices and public health - Cardoso, Marina (Saúde e Sociedade, 2020)
Over the past decade, we have seen the gradual setback of public policies for indigenous health care in Brazil, especially with regard to the basic pillars of its formulation, developed from the 1980s onwards: specific and differentiated attention, participation, and social control. This paper, despite mentioning some critical moments in this process, offers an opportunity for some reflections on how policies and practices, essentially biomedical, can be understood in the more general context of indigenous societies in the country.